2009
DOI: 10.1016/j.aquabot.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Are epiphytes a significant component of intertidal Zostera noltii beds?

Abstract: International audienceThe role of epiphytes in an intertidal Zostera noltii seagrass bed in Marennes-Oléron Bay was assessed in comparison with the other main benthic primary producers (Z. noltii, microphytobenthos) at two bathymetric levels and on a seasonal basis. Assemblage and biomass of epiphytes were studied using Scanning Electron Microscopy (SEM). Zostera noltii and its detrital matter followed a typical seasonal pattern: microphytobenthos was present in large quantities throughout the year representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 71 publications
2
46
1
Order By: Relevance
“…Seagrass leaves also represented an available substratum for bacterial colonization (Wittmann et al, 1981). In this study, the LAI of Z. noltii was relatively low compared to the range found in the literature for this species: from 0.3 to 6.6 m 2 m -2 (van Lent et al, 1991;Plus et al, 2003;Pergent-Martini et al, 2005;Lebreton et al, 2009). Nevertheless, the LAI was also higher in summer and supported a great bacterial biomass which in turn could favour the community respiration of the Z. noltii community.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Seagrass leaves also represented an available substratum for bacterial colonization (Wittmann et al, 1981). In this study, the LAI of Z. noltii was relatively low compared to the range found in the literature for this species: from 0.3 to 6.6 m 2 m -2 (van Lent et al, 1991;Plus et al, 2003;Pergent-Martini et al, 2005;Lebreton et al, 2009). Nevertheless, the LAI was also higher in summer and supported a great bacterial biomass which in turn could favour the community respiration of the Z. noltii community.…”
Section: Discussioncontrasting
confidence: 55%
“…A part of the detritus could be due to faecal material of epiphytic grazers, particularly during summer when grazing is normally the highest (Philippart, 1995). Temporal variations of leaf biomass showed a strong seasonal pattern, typical of temperate seagrasses (Duarte, 1989) and widely described for Z. noltii (Pérez-Lloréns & Niell, 1993;Philippart, 1995;Auby & Labourg, 1996;Vermaat & Verhagen, 1996;Sfriso & Ghetti, 1998;Pergent-Martini et al, 2005;Lebreton et al, 2009). They were explained by abiotic factors such as light (Philippart, 1995) and temperature (Marba et al, 1996).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This difference might be related to the longevity of the species, which is a determining factor in the process of substrate colonization by epiphytes; in some cases, this phenomenon is more evident in the older parts of the thallus (Aguilar-Rosas & Galindo 1990). In Zostera noltii, Lebreton et al (2009) found that the number of diatoms was higher on young leaves than on old leaves.…”
Section: Introductionmentioning
confidence: 88%
“…The material was collected in Lake Baikal in August 2008-2009, Bolshiye Koty Bay (N 51º54'047, Е 105º04'083) at 3 m during the vegetative activity of submerged macrophytes. The water temperature was 16°C in Bolshiye Koty Bay and 17-20 °C at other sampling sites.…”
Section: Methodsmentioning
confidence: 99%